Phase derivative thermo-spatiogram for distributed temperature sensing based on chirped grating-Michelson Interferometer - Tan, Daryl; Lim, Kok Sing; Zaini, Muhammad Khairol Annuar; Yeong, Chai Hong; Wong, Yin How; Yang, Hang Zhou; Ahmad, Harith (Elsevier, 2018)
A novel thermometric measurement based on chirped fiber Bragg grating (CFBG) and Michelson Interferometer is proposed. The interrogation technique is based on the linear relation between the temperature and the phase derivative function of the grating, which is determined through Fourier transformation of the output spectrum. The Michelson interferometer configuration offers the flexibility in adjusting the position of coupling coefficient curve in the spatiogram, enabling the interrogation to be done at a shorter optical spectrum record length which can reduce the interrogation time and computation load.